Antibacterial and antifungal potentials of the solvents extracts from Eryngium caeruleum, Notholirion thomsonianum and Allium consanguineum. Issue 1 (December 2016) - Sadiq, Abdul; Ahmad, Sadiq; Ali, Rahmat; Ahmad, Fawad; Ahmad, Sajjad; Zeb, Anwar; Ayaz, Muhammad; Ullah, Farhat; Siddique, Abu
Abstract Background Herbal medicines have long been used for various ailments in various societies and natural bioactive compounds are gaining more and more importance due to various factors. In this context, three plant species i.e., Eryngium caeruleum, Notholirion thomsonianum andAllium consanguineum have been aimed for the scientific verification of their purported traditional uses against various infectious diseases. Methods In this study, three plants were assayed for antibacterial and antifungal potentials. The antibacterial investigations were performed via well diffusion method and nutrient broth dilution method. The bacterial strains used in the study wereEnterococcus faecalis, Proteus mirabilis, Escherichia coli, Salmonella typhi, Klebsiella pneumonia andPseudomonas aeruginosa . The antifungal potential was investigated by dilution method of Muller-Hinton agar media of the plants' samples. The fungal strains used wereAspergillis fumigatus, Aspergillis flavus andAspergillis niger . Ceftriaxone and nystatin were used as standard drugs in antibacterial and antifungal assays respectively. Results Different fractions fromN. thomsonianum were tested against five bacterial strains while the samples fromA. consanguineum andE. caeruleum were tested against six bacterial strains. All the samples exhibited prominent antibacterial activity against the tested strains. Overall, chloroform and ethyl acetate fractions were found most potent among the three plants' samples.N. thomsonianum excelled among the three plants in antibacterial activity. Similarly, in antifungal assay, N. thomsonianum exhibited strong antifungal activity against the fungal strains. The chloroform fraction displayed MFCs of 175.67 ± 5.20***, 29.33 ± 5.48*** and 63.00 ± 4.93*** μg/ml againstAspergillus fumigatus, Aspergillus flavus andAspergillus niger respectively. The whole study demonstrates that all the three plant species were active against tested bacterial and fungal strains. Conclusion It can be concluded from our findings thatN. thomsonianum, A. consanguineum andE. caeruleum have broad antibacterial and antifungal potentials. In all of the plants' samples, chloroform and ethyl acetate fractions were more active. Furthermore, being the potent samples, the chloroform and ethyl acetate fractions of these plants can be subjected to column chromatography for the isolation of more effective antimicrobial drugs.